Amino Acid Substitutions Associated with Avian H5N6 Influenza A Virus Adaptation to Mice - Zhang, Chunmao; Zhao, Zongzheng; Guo, Zhendong; Zhang, Jiajie; Li, Jiaming; Yang, Yifei; Lu, Shaoxia; Wang, Zhongyi; Zhi, Min; Fu, Yingying; Yang, Xiaoyu; Liu, Lina; et al. (Frontiers in Microbiology, 2017)
At least 15 cases of human beings infected with H5N6 have been reported since 2014, of which at least 9 were fatal. The highly pathogenic avian H5N6 influenza virus may pose a serious threat to both public health and the poultry industry. However, the molecular features promoting the adaptation of avian H5N6 influenza viruses to mammalian hosts is not well understood. Here, we sequentially passaged an avian H5N6 influenza A virus (A/Northern Shoveler/Ningxia/488-53/2015) 10 times in mice to identify the adaptive amino acid substitutions that confer enhanced virulence to H5N6 in mammals. The first and tenth passages of the mouse-adapted H5N6 viruses were named P1 and P10 respectively. P1 and P10 displayed higher pathogenicity in mice than their parent strain. P10 showed significantly higher replication capability in vivo and could be detected in the brains of mice, whereas P1 displayed higher replication efficiency in their lungs but was not detectable in the brain. Similar to its parent strain, P10 remained no transmissible between guinea pigs. Using genome sequencing and alignment, multiple amino acid substitutions, including PB2 E627K, PB2 T23I, PA T97I and HA R239H, were found in the adaptation of H5N6 to mice. In summary, we identified amino acid changes that are associated with H5N6 adaptation to mice.